Increasing the organic carbon stocks in mineral soils sequesters large amounts of phosphorus. (18th June 2020) - Spohn, Marie
Abstract: Despite the fact that phosphorus (P) is critical for plant biomass production in many ecosystems, the implications of soil organic carbon (OC) sequestration for the P cycle have hardly been discussed yet. Thus, the aims of this study are, first, to synthesize results about the relationship between C and P in soil organic matter (SOM) and organic matter inputs to soils, second, to review processes that affect the C:P ratio of SOM, and third, to discuss implications of OC storage in terrestrial ecosystems for P sequestration. The study shows that the storage of OC in mineral soils leads to the sequestration of large amounts of organic phosphorus (OP) since SOM in mineral soils is very rich in P. The reasons for the strong enrichment of OP with respect to OC in soils are the mineralization of OC and the formation of microbial necromass that is P‐rich as well as the strong sorption of OP to mineral surfaces that prevents OP mineralization. In particular, the formation of mineral‐associated SOM that is favorable for storing OC in soil over decadal to centennial timescales sequesters large amounts of OP. Storage of 1, 000 kg C in the clay size fraction in the topsoils of croplands sequesters 13.1 kg P. In contrast, the OC:OP ratios of wood and of peatlands are much larger than the ones in cropland soils. Thus, storage of C in wood in peatlands sequesters much less P than the storage of OC in mineral soils. In order to increase the C stocks in terrestrial ecosystems and to lock up as little P as possible, it would be more reasonable to protect and restore peatlands and to produce and preserve wood than to store OC in mineral soils. Abstract : This study shows that increasing the organic carbon (OC) stock in mineral soils sequesters large amounts of phosphorus (P) since organic matter (OM) in mineral soils is very rich in P, especially in comparison to OM inputs to soils. The reasons for the strong enrichment of organic phosphorus (OP) relative to OC in soils are the mineralization of OC and the formation of microbial necromass as well as the strong sorption of OP to mineral surfaces that decreases OP mineralization. In particular, the formation of mineral‐associated OM (MAOM) that is favorable for storing OC in soil over centennial timescales sequesters large amounts of P.